Perspective: The Lung, Particles, Fibers, Nanomaterials, and Autoimmunity - Pollard, K. Michael (Frontiers in Immunology, 2020)
Studies have shown that a wide range of factors including drugs, chemicals, microbes, and other environmental agents can induce pre-clinical autoimmunity. However, only a few have been confidently linked to autoimmune diseases. Among these are exposures to inhaled particulates that are known to be associated with autoimmune diseases such as lupus and rheumatoid arthritis. In this article, the potential of particle, fiber, and nanomaterial exposures to induce autoimmunity is discussed. It is hypothesized that inhalation of particulate material known to be associated with human autoimmune diseases, such as cigarette smoke and crystalline silica, results in a complex interplay of a number of pathological processes, including, toxicity, oxidative stress, cell and tissue damage, chronic inflammation, post-translational modification of self-antigens, and the formation of lymphoid follicles that provide a milieu for the accumulation of autoreactive B and T cells necessary for the development and persistence of autoimmune responses, leading to disease. Although experimental studies show nanomaterials are capable of inducing several of the above features, there is no evidence that this matures to autoimmune disease. The procession of events hypothesized here provides a foundation from which to pursue experimental studies to determine the potential of other environmental exposures to induce autoimmunity and autoimmune disease.